“The Hero’s Bloody Journey”: What Female Characters Encounter in Menopausal Narratives - Marambio, Soledad (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
This work employs the basic narrative structure of Joseph Campbell’s hero’s journey to analyse female protagonists in various menopause narratives found in both fiction and non-fiction books. The article focuses on the study of four texts: Darcey Steinke’s Flash Count Diary (2019), Colette’s Break of Day (1928), Dana Spiotta’s Wayward (2021), and Deborah Levy’s Living Autobiography Series (2018-2021). In his classic work, The Hero with a Thousand Faces, Campbell outlines three major stages of the hero’s journey: departure from the familiar daily world, initiation in a new, challenging world, and return to the former world with the gains obtained during the initiation. I argue that this framework is a useful tool for interpreting female characters dealing with menopause and its consequences. The daily known world of these protagonists is shaped by their pre-menopause lives and their bodies. Menopause can be viewed as the “other world” where the heroine’s initiation takes place. There, she confronts unknown forces that transform her, as she returns, changed, to her body and her daily life. I propose that in these works, this change marks both a new beginning and a continuity that the protagonists confront with a sense of rage, new places to inhabit, and fresh approaches to their bodies.